Composição corporal de cálcio e fósforo de ovelhas Santa Inês - Fernando Antônio de Souza (2009)
The trial was realized to assess the composition of calcium and phosphorus in the body of Santa Inês ewes pregnant and no pregnant submitted to two different nutritional level. Were used 39 adult animals arranged in a completely randomized design in a factorial arrangement 2 x 3 (nutritional level x number of fetuses).being nutritional level : not restricted diet (NR) and Restricted (R ),and number of fetuses: 1, 2 and 3. The animals were slaughtered following the protocol submitted to Ethics and Animal Experimentation Commitee CETEA-UFMG according to gestational age. Each animal was divided into 11 parts. The mineral solution was obtained by wet-ashed. The content of Calcium the samples was obtained by atomic absorption spectrometry and the phosphorus content by colorimetric methods . The pregnancy was the main agent responsible for changes in body among the treatments. The calcium content was the most affected among the minerals studied. The calcium concentration of the fetus wasnt affected by any of the treatments. The composition of phosphorus appeared to be less affected by the treatments used here that calcium. The phosphorus concentration was higher in the uterus, fetal fluids and mammary gland in pregnant sheep for 140 days. None of the treatments studied here caused variation in phosphorus concentration in the fetus. The level of nutritional restriction did not affect the concentration of calcium in any of the parties analyzed. But the phosphorus content of the carcass and mammary gland were reduced by the restriction. Regression analysis was realized in order to predict the amount of calcium retained in the fetus as a function of fetal mass produced. These equations showed that the calcium and phoshprus content in the fetus increases by 13 and 7 grams for each kilogram of fetus mass produced at 140 days respectively